Bellezza, biodiversità e sostenibilità: spunti dagli insegnamenti di Papa Francesco (Itinera, 2025)
Beauty, biodiversity and sustainability: insights from the teachings of Pope FrancisThis research aims to trace the elements directly related to the theme of beauty contained in the teachings of Pope Francis that can contribute to the protection of biodiversity, which he calls the “web of life” given to us by God. The fact that his teachings have the potential to guide the actions of Catholic believers makes a study of their content pertinent. Since 2013, Pope Francis has been at the head of a structure in which pronouncements – especially the most authoritative texts such as an encyclical letter – are promoted, commented, transposed, and culturally adapted to various contexts and levels from national to local, not forgetting numerous transnational thematic networks and religious congregations. This ensures a very wide and capillary dissemination of documents such as the famous 2015 encyclical Laudato si’ on the care of the common home. The nexus between beauty and biodiversity (more broadly care for creation) has, of course, already been mentioned in a number of articles and essays; nevertheless, it is a topic that has so far been relatively little explored and deserves more attention. The first part of this article analyzes the nexus between beauty and the protection of biodiversity in the speeches and writings of Pope Francis. The second part presents some avenues for action, focusing in particular on education and the integral dimension.